Sourgrass control in response to the association of 2,4-d to ACCase inhibitor herbicides (Bioscience Journal, 2020)
ACCase inhibitor herbicides are widely used to control poaceae such as sourgrass (Digitaria insularis). However, these herbicides are selective for eudicots, which requires the use of broadleaf herbicides in areas with broadleaf and narrow leaf weeds. The objective of this study was to evaluate the effect of the association ACCase inhibitors and 2,4-D for the control of sourgrass. Two experiments were carried out under greenhouse conditions. The first experiment evaluated the effect of associating 2,4-D and graminicides to control of sourgrass, using dose-response curves for the herbicides clethodim, quizalofop-P-tefuril and clethodim + quizalofop-P-tefuril. In the second experiment, due to the results of the first one, the necessary period between the application of 2,4-D and the graminicides was evaluated in order to avoid antagonism in sourgrass. The results show that the herbicide clethodim, at the recommended dose, has its efficiency reduced in about 8% when applied in association with 2,4-D. As for the herbicide quizalofop-P-tefuril, this effect was higher, causing a reduction of 39% in control. However, the association of 2,4-D to the mixture of clethodim + quizalofop-P-tefuril did not result in antagonism. It takes nine and 12 days between the application of 2,4-D and the graminicides clethodim and quizalofop-P-tefuril, respectively, for there to be no antagonism.